Analysis of the Readiness of Lectures in Mathematics Education Study Program to Implementation of the Independent Learning Curriculum for Independent Campus (MBKM - Mardika, Fitria; Putri Utami, Nita (JTMT: Journal Tadris Matematika, 2024)
This research aims to determine the readiness of lectures in mathematics education study program to implement the Free Learning Curriculum and Independent Campus (MBKM). The readiness of lecturers is assessed based on four aspects: MBKM information, understanding of MBKM, response to MBKM, and MBKM program. The population consisted of eight permanent lecturers in mathematics Education study program. The sample was selected using the total sampling technique, so the number of samples in this study was 8 people. Data collection techniques in the form of lecturer readiness questionnaires and interviews The results indicate that the percentage of lecturer readiness for each indicator is: (1) 63.5% for the MBKM Information indicator; (2) 64.06% for the Understanding of MBKM indicator; (3) 70.49% for the Response to MBKM indicator; and (4) 65.63% for the MBKM Program indicator. Overall, the percentage of lecturer readiness is 66.5%, in the category of sufficient. This means that mathematics education lecturers are sufficiently prepared for the implementation of the Free Learning Curriculum and Independent Campus. Various efforts are needed to enhance the readiness of lecturers across all indicators.